The impact of Islamic attributes of destination and religiosity on Muslim tourists' satisfaction / Eiman Mandili - Mandili, Eiman (2011)
The aim of this study is to study the impact of Islamic attributes of destination and religiosity on overall Muslims tourists’ satisfaction. The main concern of this paper is to emphasize the importance of Islamic religiousness and how it affects on tourists satisfaction, and Islamic Attribute of Destination factors. Muslim tourists' demand for Islam attributes learning in advertising directed at potential clients is a substantial weakness in some countries’ considered tourism. Tourism satisfaction in modern countries and Islamic culture has received great concentration from researchers. The key to determine tourism incentive is to see holiday travel as a satisfier of the needs and wants. Religiosity has become an important target area in the business human beings so it has become imperative for Islamic tourism to have insights about faith of Muslims tourists for their well-being. Overall, fairly moderate evidence questionnaires of religiosity are applicable to most religions of the world. On the basis of this site of study authors have developed researches for Islamic destination to develop a scale that can gauge Islamic religiosity in more objective terms. The study also investigate the need to measure Islamist religiosity as Muslims make a larger chunk of international tourism; On other hands that to accomplish full fruits of globalization Islamists population cannot be neglected that from business world. So in order to manage diversity in hospitality factors, understanding the religious orientations can furnish fruitful contributions for the success of the hospitality organization. International hospitality should take into account Islamic religiosity as a major factor while planning to diversify their businesses to Muslim world.